An Analysis of Head Nurses’ Nursing Informatics Competencies and Nurses’ Attitudes towards Patient Safety in Hospitals - Suganda, Tomy; Handiyani, Hanny; Rachmi, Shanti Farida; Masyati, Eti; Rahman, La Ode Abdul (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Introduction: Improving patient safety attitudes will provide quality care and a safe environment and practice for patients. The attitude of nurses towards patient safety in hospitals still requires improvement and improvement efforts. The assessment of nurses’ attitudes toward patient safety can be used as a reference for preparing programs to maintain quality and patient safety in hospitals. Objectives: This study aimed to determine the relationship between head nurses’ nursing informatics competencies and nurses’ characteristics and attitudes towards patient safety. Methods: A cross-sectional study involving 251 nurses at a hospital in Jakarta was conducted. The Nursing Informatics Competency Assessment Tool and the Safety Attitudes Questionnaire with demographic information were used for data collection. Results: Overall, nurses’ attitudes towards patient safety showed a median value of 141 (80.18% of the maximum value), and the mean value of head nurses’ nursing informatics competency was 99.53 (66.35% of the maximum score). This study showed a significant relationship between head nurses’ nursing informatics competencies and nurses’ attitudes toward patient safety. Nursing informatics competencies, computer literacy, informatics literacy, and informatics management skill significantly influenced patient safety attitudes (p<0.05). Conclusion: Nursing informatics competence is the basis for nurses to respond to the development of health management information systems and technology in modern healthcare environments. Nursing informatics competence of the head nurses’ encourages the success of the head nurses’ following the rapid development of information, it will have